2020
DOI: 10.1038/s41598-020-66583-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust combination of liver stereotactic body radiotherapy modulates pharmacokinetics of sorafenib toward preferable parameters

Abstract: To evaluate the effect and mechanism of radiotherapy (RT)-sorafenib pharmacokinetics (PK) in different regimens with conventional or high dose irradiation. Between February 2012 and December 2018, 43 patients with portal vein tumor thrombosis treated with sorafenib plus conventional RT (58%) or stereotactic body radiation therapy (SBRT, 42%) were retrospectively reviewed. In vivo and in vitro studies of concurrent and sequential RT with sorafenib were designed. SBRT resulted in a 3-fold increase in complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 44 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…Moreover, preclinical data from studies combining sorafenib and RT have suggested improved efficacy in HCC cell lines both in vitro and in vivo [ 21 , 22 ]. Additionally, the efficacy of RT with sorafenib in patients with unresectable HCC has been reported [ 7 , 8 ]. Moreover, the AUC of sorafenib can be modulated by RT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, preclinical data from studies combining sorafenib and RT have suggested improved efficacy in HCC cell lines both in vitro and in vivo [ 21 , 22 ]. Additionally, the efficacy of RT with sorafenib in patients with unresectable HCC has been reported [ 7 , 8 ]. Moreover, the AUC of sorafenib can be modulated by RT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A freely moving rat model was designed for the current study [ 8 ]. The rats were anesthetized and immobilized on a board while undergoing computed tomography to localize the whole liver or a central area measuring 1.5 cm × 1.5 cm for the SBRT technique.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations